Complete mitochondrial genome of the blister beetle Hycleus scutellatus Rosenhauer, 1856 (Coleoptera, Meloidae). Issue 6 (3rd June 2022) - Mora, Pablo; Montiel, Eugenia E.; Palomeque, Teresa; Lorite, Pedro
Abstract: In this study, we report the complete mitochondrial genome or mitogenome of the blister beetle Hycleus scutellatus, one endemic species from the Iberian Peninsula. The mitogenome was 16, 035 base pairs in length, with an A + T content of 71.7%. It has 37 genes including 13 protein-coding genes, 22 transfer RNA genes and 2 ribosomal RNA genes. To analyze the evolutionary position of H. scutellatus, we constructed a phylogenetic tree using all available mitogenomes from species of the family Meloidae. The results show that Hycleus species are very close to the genus Mylabris . We present here the mitogenome of H. scutellatus as a new resource to elucidate the phylogenetic relations among the Meloidea family, being this source very useful for future evolutionary analyses of blister beetles.